Supramolecular nucleoside-based gel: molecular dynamics simulation and characterization of its nanoarchitecture and self-assembly mechanism - Angelerou, Maria G.F.; Frederix, Pim W.J.M.; Wallace, Matthew; Yang, Bin; Rodger, Alison; Adams, Dave J.; Marlow, Maria; Zelzer, Mischa (American Chemical Society, 2018)
Among the diversity of existing supramolecular hydrogels, nucleic acid-based hydrogels are of particular interest for potential drug delivery and tissue engineering applications because of their inherent biocompatibility. Hydrogel performance is directly related to the nanostructure and the self-assembly mechanism of the material, an aspect that is not well-understood for nucleic acid-based hydrogels in general and has not yet been explored for cytosine-based hydrogels in particular. Herein, we use a broad range of experimental characterization techniques along with molecular dynamics (MD) simulation to demonstrate the complementarity and applicability of both approaches for nucleic acid-based gelators in general and propose the self-assembly mechanism for a novel supramolecular gelator, N4-octanoyl-2′-deoxycytidine. The experimental data and the MD simulation are in complete agreement with each other and demonstrate the formation of a hydrophobic core within the fibrillar structures of these mainly water-containing materials. The characterization of the distinct duality of environments in this cytidine-based gel will form the basis for further encapsulation of both small hydrophobic drugs and biopharmaceuticals (proteins and nucleic acids) for drug delivery and tissue engineering applications.